Klasifikasi Penjualan Provider Pulsa di Kecamatan Masbagik Lombok Timur Menggunakan Metode Naïve Bayes - Musfita, Nurul; Fitriyani, Nurul; Baskara, Zulhan Widya; Zulhan Widya Baskara (ESTIMASI: Journal of Statistics and Its Application, 2023)
The rapid development of technology causes the use of mobile phones and the need for pulses to increase. East Lombok is the area with the largest population in NTB and high users of information technology. East Lombok also has an internet network or smooth communication signal, which shows that there are many providers in the area. To see the types of providers that are widely used in Masbagik District, East Lombok, taking into account the largest population, a classification is made of whether these providers are in demand or not using the Naïve Bayes method. This study aims to determine the classification results and the accuracy of the sales classification of credit providers. The data is split into two categories: training data (90%) and testing data (10%). According to the findings of the study, 225 of the 309 testing data were correctly classified. The resulting APER value is 27.2%, which indicates that the accuracy of the classification results using the Naïve Bayes method is 72.8%. An AUC value of 0.804 was also obtained, which means that the accuracy of the classification of selling pulse providers that are in demand, moderately in demand, and not in demand was sufficient.